In Vitro Antibacterial and Antibiofilm Activity of Lippia alba Essential Oil, Citral, and Carvone against Staphylococcus aureus - Emanuela Mesquita Porfírio; Hider Machado Melo; Antônio Matheus Gomes Pereira; Theodora Thays Arruda Cavalcante; Geovany Amorim Gomes; Mário Geraldo de Carvalho; Renata Albuquerque Costa; Francisco Eduardo Aragão Catunda Júnior (The Scientific World Journal)
In vitro antimicrobial and antibiofilm activities of the Lippia alba essential oil and its major components (citral and carvone) against Staphylococcus aureus were investigated. Essential oils (LA1EO, LA2EO, and LA3EO) were extracted from the aerial parts of three L. alba specimens by hydrodistillation and analyzed by gas chromatography coupled to a mass spectrometer. Minimum Inhibitory Concentrations (MIC) and Minimum Bacterial Concentration (MBC) were determined by the microdilution method. For the antibiofilm assays, the biomass formation in the biofilm was evaluated by the microtiter-plate technique with the crystal violet (CV) assay and the viability of the bacterial cells was analyzed. All oils and their major components presented antibacterial activity, and the lowest MIC and MBC values were 0.5 mg mL−1 when LA1EO and citral were used. Potential inhibition (100%) of S. aureus biofilm formation at the concentration of 0.5 mg mL−1 of all EOs was observed. However, the elimination of biofilm cells was confirmed at concentrations of 1 mg mL−1, 2 mg mL−1, 2 mg mL−1, and 0.5 mg mL−1 for LA1EO, LA2EO, LA3EO, and citral, respectively. The results obtained in the present research point to the promising antibacterial and antibiofilm potential of L. alba EOs against S. aureus, a species of recognized clinical interest.